Real-World Use of Generic Meropenem: Results of an Observational Study - Santiago Garnica-Velandia; Luz Adriana Aristizábal-Ruiz; Carlos Arturo Alvarez-Moreno (MDPI AG, 2021)
Background: To determine the therapeutic effect and tolerability of meropenem in routine clinical practice, in terms of clinical and microbiological response. Methods: A real-world, observational, descriptive, longitudinal study with daily monitoring of clinical history records was conducted on all patients who were medically prescribed meropenem during a period between October 2015 and March 2016 at a university hospital in Bucaramanga (Colombia). Results: The study evaluated 84 patients with an average age of 63.2 years, mostly older adults with multiple comorbidities, of whom 54.8% were men. A positive clinical or microbiological response was obtained in 98.8% of the patients. At the end of the treatments, significant improvements in dysthermia (0% vs. 29% at the beginning, p = 0.000), tachycardia (13% vs. 47%, p = 0.049), and leukocytosis (39% vs. 15% at the beginning, p = 0.008) were evidenced. The improvement in the indicator that combines all the Systemic Inflammatory Response Syndrome (SIRS) criteria was also significant (p = 0.000). The treatment was well tolerated, although we identified some non-serious and expected adverse reactions. Conclusions: Generic meropenem proved to be effective and well tolerated for different types of infection in routine clinical practice. The results are consistent with the findings of the clinical studies with the innovator drug.